DEVELOPMENT OF AN INFORMAL APPROACH-BASED LEARNING MODEL TO IMPROVE LECTURERS' ENGLISH SKILLS - Srisaramout, Bancharat (Edu Learning, 2025)
This research is a type of development research that aims to develop an English learning model for lecturers in the Education Management Study Program to help prepare lecturers to teach bilingual classes. This can also help improve the quality and international scale learning process of the Education Management Study Program. The obstacle found in the field is that there are still many lecturers who have not mastered English either passively or actively. Based on the results of the pre-test using the performance test method given to 25 lecturers which was conducted randomly, it showed that 82% of lecturers had basic English skills and 22% of lecturers had intermediate English skills. Looking at the results of the performance test, it shows that the lecturer's ability to communicate in English is low. The research procedure used is using three stages, namely: 1) preliminary stage, 2) model development stage, 3) trial stage, 4) implementation stage. The results of the study stated that the results of the development of an English learning model based on the informal method could improve the English competence of lecturers.